BUDAYA KERJA DAN MOTIVASI KERJA GURU DI SDN 1 SUKACARI BATANGHARI NUBAN LAMPUNG TIMUR - Sandi Nismun; Ahmad Rifa’i Abun; Rina Setyaningsih (UNISAN JURNAL, 2023)
The purpose of this study was to determine work motivation and work culture. This study uses a qualitative approach. While the method used in this research is descriptive research method. The data collection technique used is observation, interview and documentation techniques. work culture is a philosophy as the values ​​that become the nature, habits, and driving forces that are shared by every individual in the work environment of an organization. Work motivation can be interpreted as a psychological process that reflects the interaction between attitudes, needs, perceptions, and decisions that occur in a person.